The effect of the native kinematics of the knee on the outcome following total knee arthroplasty - Mooney, L.; Smith, Anne; Sloan, K.; Clark, G. (British Editorial Society of Bone and Joint Surgery, 2016)
Aims: The aim of this study was to investigate differences in pain, range of movement function and satisfaction at three months and one year after total knee arthroplasty (TKA) in patients with an oblique pattern of kinematic graph of the knee and those with a varus pattern. Patients and Methods: A total of 91 patients who underwent TKA were included in this retrospective study. Patients (59 women and 32 men with mean age of 68.7 years; 38.6 to 88.4) were grouped according to kinematic graphs which were generated during navigated TKA and the outcomes between the groups were compared. Results: The graphs were varus in 50 patients (55%), oblique in 19 (21%), neutral in 17 (18.5%) and valgus in five (5.5%). After adjustment for pre-operative scores and gender, compared with patients with varus knee kinematics, patients with an oblique kinematic graph had a poorer outcome with lower Knee Society scores at three months (9.2 points, p = 0.038). Conclusion: We found four distinct kinematic graphs in knees and that patients with an oblique graph have a poorer outcome in the short-term after TKA.